Analysis of Work Experience, Emotional Issues, and Training on Employee Employment Ability at PT Bank Negara Indonesia (Persero) Tbk Branch Office Rantau Prapat North Sumatra - Halimatussa'diah (International Journal of Management, Economic and Accounting, 2023)
This study aims to find out how the influence of Work Experience (X1), Emotional Issues (X2), and Training (X3) on the Work Ability (Y) Employees at PT Bank Negara Indonesia (Persero) Tbk Office Branch Rantau Prapat North Sumatera. The population in this study is the entire Employee at PT Bank Negara Indonesia (Persero) Tbk Office Branch Rantau Prapat North Sumatera which has 50 permanent employees. The sample was taken as a population of 49 respondents not including the head of the Branch. The research was conducted from April to June 2023. This study uses quantitative data processed with SPSS version 20.0 with a dual linear regression model. The results of the study showed that Work Experience had a positive and significant impact on the employability of PT Bank Negara Indonesia (Persero) Tbk Office Branch Rantau Prapat North Sumatera. Based on the result of 7,345 while the table was 2,012 and significant of 0,000, so that the number of 7,335> tables 2,012 is significant and significant 0,000< 0,05. Emotional issues have a positive impact and significant effect on the employment capacity of PT Bank Negara Indonesia (Persero) Tbk Office Branch Rantau Prapat North Sumatera. Work experience, emotional issues, and training have a positive and significant impact on the employability of employees at PT Bank Negara Indonesia (Persero) Tbk Office Branch Rantau Prapat North Sumatera. Based on the result, F is larger than the Ftable, because 25,578 is bigger than 2,81